DESIGNING AN AFFECTIVE-INTEGRATED INSTRUCTIONAL SYSTEM BASED ON PANCASILA STUDENT PROFILE IN PRIMARY EDUCATION: A DESIGN-BASED RESEARCH - Maria Nainggolan; Sumarno; Wawan Bunawan; Alfa Kristin Laia (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2026)
The implementation of learning in Indonesian primary education remains predominantly cognitive-oriented, while affective dimensions are insufficiently integrated into instructional system design. This condition creates a gap between the objectives of character education and actual classroom practices. This study aimed to design an affective-integrated instructional system based on the Pancasila Student Profile through a Design-Based Research (DBR) approach. The study was conducted at UPT SDN 066652 Medan Helvetia involving 44 fifth-grade students. The research employed four iterative stages: analysis, design, implementation, and revision. Data were collected through classroom observation, interviews, instructional document analysis, reflective journals, and affective assessment instruments. Quantitative data were analyzed using descriptive statistics and N-Gain analysis, while qualitative data were analyzed using reflective thematic analysis. The findings revealed that the instructional system developed in this study explicitly integrated cognitive and affective domains into all instructional components, including learning objectives, contextual and collaborative learning activities, reflective learning processes, and authentic affective assessment. The instructional system facilitated the development of cooperation, independence, creativity, critical reasoning, communication confidence, and social responsibility aligned with the dimensions of the Pancasila Student Profile. The implementation process also transformed classroom interaction from teacher-centered instruction into collaborative and reflective learning experiences. The study generated several instructional design principles emphasizing contextual learning, value internalization, reflective interaction, collaborative engagement, and continuous affective assessment. The findings indicate that Design-Based Research provides an effective framework for developing holistic instructional systems integrating cognitive and affective learning dimensions in primary education.